Individualism and identity: resistance to speed cameras in the UK - Wells, H; Wills, D (Cranfield University, 2012)
As a surveillance technology, speed cameras have produced significant levels of resistance from the general (driving) public. This resistance has not, however, drawn on the kinds of civil liberties or 'Big Brother' narratives that might be expected. Using this context as a case study, this paper suggests that significant resistance to surveillance practices may emerge when surveillance technologies produce data doubles that are antagonistically incompatible with those identities which have emerged 'organically' from the resisting individuals and communities.In this example, the self-ascribed identity of normal, respectable, non-criminal drivers is threatened by technologies of risk and 'techno-fixes' which (through their operation) construct identities as risk- carrying, deviant, and criminal The sense of unfairness generated by this conflict between how we see ourselves and how the disciplining state sees us generates a sense of injustice. This sense of injustice is fertile ground for resistance. The paper identifies three main narrative themes in discourses of resistance to speed cameras, including the rejection of the official expertise used to justify surveillance and punishment, and the construction of a narrative which positions the drivers as an ordinary person resisting an oppressive state. The final narrative highlights the danger posed by other groups which, being constructed as genuinely and uncontroversially deviant, are more worthy of surveillant attention. As such, the paper suggests that, while offering fertile ground for the generation of resistant strategies, the speed camera context produces a very particular, very individualised, type of resistance which may actually contribute to existing processes of discrimination and 'othering' amongst surveilled populations.